ANALISIS PEMILIHAN MODEL PREDIKTOR FINANCIAL DISTRESSTERBAIK (PERBANDINGAN ANTARA THE ZMIJEWSKI MODEL, THE OHLSON MODEL, THE ALTMAN MODEL, DAN THE SPRINGATE MODEL) - Susandra, Farizka (Fakultas Ekonomi Universitas Djuanda, 2015)
This study aims to choose the best financial distress models between The Zmijewski Model, The Ohlson Model, The Altman Model and The Springate Model in manufacturing industries listed in the Indonesia Stock Exchange. Samples from this study are industries that satisfied the criteria of purposive sampling. This study took the 2006 - 2007 period is estimated as the sample, and 2008 - 2009 as the year of the validation samples. SPSS 16.0 is applied to process the data of this study. The model used to test the hypothesis logistic regression (logit) analyzes were applied SPSS 16.0.Logistic regression (logit) analysis shows that the Zmijewski Model, The Ohlson Model, The Altman Model and The Springate model can be used to predict financial distress. Meanwhile, both the Zmijewski Model, The Ohlson Model, The Altman Model and The Springate model can be used to predict financial distress, financial difficulties of prediction accuracy rate of the companies listed in the Indonesia Stock Exchange using the Springate model is 25.2% higher than the 1.3% Zmijewski Model, The Ohlson Model of 22.7% and 15% of The Altman model.Keywords: Financial Distress, logit, Zmijewski, Ohlson, Altman, Springate.